2004
DOI: 10.1002/cncr.20347
|View full text |Cite
|
Sign up to set email alerts
|

The risk of venous thromboembolic disease associated with adjuvant hormone therapy for breast carcinoma

Abstract: BACKGROUNDTamoxifen therapy for patients with breast carcinoma is perceived as an independent risk factor for venous thromboembolic events (VTE), but the risk associated with other adjuvant therapies is less well recognized.METHODSThe authors conducted a computerized PubMed literature search for English‐language articles published between January 1966 and December 2003. Studies were analyzed with regard to trial design, breast carcinoma staging, adjuvant agent, definition of VTE outcomes, method of VTE case as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
9

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(86 citation statements)
references
References 104 publications
(133 reference statements)
3
73
1
9
Order By: Relevance
“…The magnitude of increase in risk of VTE we observed after beginning tamoxifen therapy was comparable to that in studies of women with early-stage breast cancer between 1989 and 1999, which report an excess risk of VTE events in women receiving tamoxifen between 1.5-fold and sevenfold. 30 Our results are also concordant with those from a large cohort of women from Denmark with early-stage breast cancer in which women treated with tamoxifen had a 3.5-fold higher risk of VTE than women receiving other treatments. 10 Previous research has found the influence of tamoxifen on risk of VTE to attenuate 1 to 2 years after beginning therapy, 10,31 possibly suggesting an adaptation of the hemostatic system to the procoagulant effects of tamoxifen.…”
Section: 2supporting
confidence: 88%
“…The magnitude of increase in risk of VTE we observed after beginning tamoxifen therapy was comparable to that in studies of women with early-stage breast cancer between 1989 and 1999, which report an excess risk of VTE events in women receiving tamoxifen between 1.5-fold and sevenfold. 30 Our results are also concordant with those from a large cohort of women from Denmark with early-stage breast cancer in which women treated with tamoxifen had a 3.5-fold higher risk of VTE than women receiving other treatments. 10 Previous research has found the influence of tamoxifen on risk of VTE to attenuate 1 to 2 years after beginning therapy, 10,31 possibly suggesting an adaptation of the hemostatic system to the procoagulant effects of tamoxifen.…”
Section: 2supporting
confidence: 88%
“…Raloxifene increases the risk of VTE similarly to what has been observed with tamoxifen and E use in postmenopausal women (4,(12)(13)(14). In the Multiple Outcomes of Raloxifene Evaluation (MORE) trial, the risk of venous thromboembolic disease (deep venous thrombosis or pulmonary embolism) was found to be 3.1 times higher (95% confidence interval, 1.5 to 6.2) in women assigned to the raloxifene group than to the placebo group.…”
Section: Discussionmentioning
confidence: 74%
“…В исследованиях по профилактическому применению тамоксифена у здоро-вых женщин отмечено двукратное повышение относи-тельного риска венозных тромбоэмболических событий, исключая тромбофлебиты поверхностных вен (ОР 1,9, 95% ДИ 1,4-2,6, р<0,0001) [41]. Эти риски сопоставимы с таковыми при приеме оральных контрацептивов или заместительной гормональной терапии [42]. Такая же закономерность отмечена и в адъювантных исследовани-ях: в группе тамоксифена отмечалось 1,5-7,1-кратное увеличение риска венозной тромбоэмболии по сравне-нию с плацебо, хотя 40% событий регистрировались после крупных хирургических вмешательств, т. е. были ситуационными [42].…”
Section: тромбоэмболические осложненияunclassified